Penerapan Teknologi Pembuatan Pakan Ikan Berbahan Baku Ampas Tahu untuk Peningkatan Kualitas Ikan Lele dan Ekonomi Usaha Ikan Lele Rumahan di Kelurahan Asam Kumbang - Asyiah, Nur; Ariani Safitri, Sri; Karima Wardani, Dwika (Universitas Medan Area, 2022)
The purpose of this research is to apply the technology of making fish from tofu dregs to improve the quality of catfish and the economy of home-based catfish business in Asam Village. The tofu dregs used were obtained from the tofu and tempeh Home Industry in the Asam Kumbang Village area. The composition of the raw material for making catfish feed used is 80% tofu dregs + 20% shrimp head. The catfish feed that has been made is then tested for characteristics, namely protein 43.87%, fat 25.04%, carbohydrates 68, 73%. Observations were made for 42 days on catfish that were given fish feed from tofu dregs or those that were not given. The results obtained during 42 days of feeding fish from tofu waste with observations made on days 7, 14, 21, 28, 35 and 42 with the average weight (weight) of each fish (grams): 21, 58 , 92, 147, 193 and 240. Catfish that are ready to harvest have 5-6 tails per kg with the physical characteristics of large/fat fish. The cost of purchasing catfish seeds is Rp. 25 and the cost of making fish feed from tofu dregs for availability for 42 days (harvest mass) is Rp. 12,250. The catfish harvest period per kg is 5 fish and the selling price to the catfish seller is IDR 20,000 / kg. The catfish harvest for 42 days was 5 kg with a total selling price of Rp. 100.00. So the profit obtained from the sale of 4 kg of catfish is Rp. 87,750 or Rp. 3,500/head.Â